Local Food Resources, Food Security, and Regional Economic Outcomes: A North Sulawesi Empirical Model - Parasan, Pradipta Mandasari (Efficient: Indonesian Journal of Development Economics, 2025)
This research aims to analyze the influence of local food resources on food security and its impact on the local economy. The background of the research departs from the condition of North Sulawesi Province which has unique geographical characteristics with abundant natural resources, agriculture, and fisheries. Nevertheless, this region still faces challenges in the form of dependence on food supply from outside, fluctuations in commodity prices, and suboptimal economic diversification based on local potential. The research method used is to use a quantitative approach with path analysis using SEM-PLS. Primary data was obtained from 82 respondents involved in local food management and utilization. The results of the study show that food security has a direct and significant effect on the local economy. Local food resources have also been shown to have a direct and significant effect on food security, but do not have a direct effect on the local economy. In addition, there is a significant indirect influence of local food resources through food security on the local economy. This research is expected to contribute to the government as a policymaker in encouraging food security based on local potential to improve the local economy, especially in North Sulawesi Province.